القيم الروحية والتربوية في شعر عمر بهاء الدين الأميري - كرباع, علي (جامعة الوادي university of eloued, 2022)
تسعى هذه الورقة البحثية في تحديد بعض القيم الروحية والتربوية التي جسّدها الشاعر عمر بهاء الدين الأميري في شعره,إذ كانت منبثقة من ثقافته الدينية المستوحاة من الكتاب والسيرة النبوية الشريفة, فالشاعر رغم كونه رجل سياسة إلا أن ذلك لم يمنعه من نظم شعر متزن وملتزم ليكون رسالة تبليغية عن سماحة الدين الإسلامي . وإن التطرق لهذه للقيم في شعره يتجلى في استحضار البعد الديني المتمثل في العقائد كالإيمان بالله ورسوله والقدر, والعبادات كالصلاة والحج والعمرة والصيام والدعاء, أما البعد التربوي فقد تضمن الأخلاق والمعاملات والسلوكيات , فجاء النصح والتفاؤل والكفاح والصبر. في ختام هذا المقال جاءت الخاتمة متضمنة التنائج التي تم التوصل إليها ومنها أن الأميري قد جعل من الشعر أداة تبليغية عن الإسلام , وهذا ما يسمى بالأدب الإسلامي . This paper seeks to identify some of the spiritual and educational values that the poet Omar Bahaa Al-Din Al-Amiri embodied in his poetry, as it was emanated from his religious culture inspired by the Quran and the Sunnah. Al-Amiri was a man of politics despite that he was able to write engaged poems that report tolerance of the Islamic religion. These values in his poetry are reflected in the religious dimension represented in beliefs such as belief in God and His Messenger and destiny, and acts of worship such as prayer, Hajj, Umrah, fasting, and Duaa. As for the educational dimension, it included morals, transactions, and behaviors, so advice, optimism, struggle, and patience came. The conclusion includes the results that were reached, which include among others that Al-Amiri has made poetry a tool for informing about Islam, and this is what is called Islamic literature
مقال
Keywords: الأدب الإسلامي ; النقد الأخلاقي ; القيم الر ; حية ; البعد الديني ; الجمالية